Kłamstwo jako strategia adaptacyjna - Janda-Dębek, Bożena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The essence of this publication is to present the theoretical approach, according to which the lie is seen as a specific behaviour strategy of an individual commonly applied in all kinds of life situations. Anyway, from the view point of the lying person it is frequently the most effective strategy. In many cases this strategy is accepted or even imposed by the community - in many situations not to apply this strategy can be rather an indication of lack of social competencies than a manifestation of social pathology. In this article also an own definition of lie and factors conditioning situations when lie occurs are presented. We have also categorised the situations, in which lie has the character of adaptation behaviour. Furthermore research results have been presented proving that -regarding the personality features - liars do not differ from so-called ordinary people.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 199-213